Greece and the European Union: The Greek Approach to the lntergovernmental Conference - Christakis, Michalis (Études helléniques / Hellenic Studies, 1998)
This article examines the role that Greece played during the European Intergovernmental Conference. The author gives the Greek perspective by asking a series of questions on Europe’s social dimension, the development of European institutions and Common Foreign and Security Policy.